Where I end & you begin - Norton, Preston, 1985- (Hyperion, 2019)
As punishment for breaking into their high school to watch the solar eclipse, Ezra, his crush Imogen, Ezra's best friend Holden, and Imogen's best friend Wynonna must perform in the school's production of Shakespeare's Twelfth Night, but before the first rehearsal starts, socially inept Ezra and badass Wynonna wake up in each other's bodies.